(untitled) - Vaughan, Andrew (Oxford, 2009)
Content: offering a variety of different accents in the listening exercises and the special viewpoints sections that feature a wide range of people talking about aspects of business and culture.
Keywords: English language,Vocabulary,Tiếng Anh; Business English,Tiếng Anh thương mại